Panchayati Raj System and Rural Development: Challenges and Opportunities. - Ravi, Venkata R. and Raj, D. (2006)
The paper is an attempt to take up the debate on the methods of enabling people to participate in the development process. It focuses on the emerging challenge posed by the process of decentralization of authority and devolution of responsibility at the village level. This is done by way of critically examining the issues of guaranteeing employment to rural populations besides the provision of water for drinking and irrigation. Matters relating to capacity building of the chief functionaries at the panchayat level to enhance good governance and management have also been covered. Suggestions have also been given so as to ensure that local governance is made more transparent and accountable at the level of PRIs and Urban Local Bodies. All this is recommended for bringing about a greater match between the people’s needs and the implementation of their village plans.